Health in Portugal under the Troika: What Happened to Health Reform and to Health System Performance? - Crisóstomo, S.; Silva, M. (The Welfare State in Portugal in the Age of Austerity, 2014)
The major purpose of this paper is to review the main changes in the Portuguese National Health Service (SNS) features and performance that may result from the new wave of austerity shaped by the Program of Financial Assistance. The implementation of policy measures in the initial MoU is monitored and success in achieving their goal(s) is evaluated. For comparative purposes, data on key indicators of health system performance (namely concerning health care access and financing, and health status) are analyzed before and after the initial MoU. Data sources include the original MoU and its updates, review reports from the EC and the IMF, official journals, and the OECD and WHO health databases. Policy measures implemented and not, changed, replaced or withdrawn from the MoU are identified. Sectors and measures where implementation was more successful and implementation obstacles are also identified. Finally, the extent of changes in programs that derive from the MoU and the system performance itself will be assessed, in order to determine if there are changes with implications concerning the constitutional principles of the SNS: Is the universality in danger? Has the SNS lost its comprehensiveness? Has the rise of copayments resulted in new access issues?